Characterization of Pulmonary Sclerosing Pneumocytoma Assessed by 18F‐FDG PET/CT - Jie Xu; Xing Wan; Shudan Zhai; Shuai Yuan; Songyi Li; Wengui Xu; Mengran Fan; Lei Zhu (Thoracic Cancer, 2025)
ABSTRACT Background This study evaluated the presentation of pulmonary sclerosing pneumocytoma (PSP) in 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG PET/CT) with the aim of increasing awareness of the disease. Methods Retrospective analysis was performed on 46 PSP patients who had 18F‐FDG PET/CT before surgery or pathological examination from January 2011 to December 2023. The 18F‐FDG PET/CT manifestations of PSP were summarized, and the correlation between the maximum diameter of the tumor and PET metabolic parameters was analyzed, including the maximum standardized uptake value (SUVmax), the mean SUV (SUVmean), the peak SUV (SUVpeak), metabolic tumor volume (MTV) and total lesion glycolysis (TLG). Results The 46 tumors were randomly distributed in each lobe of both lungs. The mean maximum diameter of these lesions was 2.2 cm (range: 0.6 to 6.5 cm). The mean SUVmax was 2.96 ± 1.88 (median: 2.69, range: 0–9.02). Thirty‐three cases were categorized as mild to moderate FDG uptake, eleven cases were categorized as intense FDG uptake, and no FDG uptake was observed in the remaining two cases of the lesions qualitatively evaluated. The SUVmax of the PSP showed a positive correlation with the maximum diameter of the tumors (R = 0.493, R2 = 0.258, and p < 0.001). SUVmean (R = 0.500, R2 = 0.259, p < 0.001), SUVpeak (R = 0.553, R2 = 0.324, p < 0.001), MTV (R = 0.773, R2 = 0.592, p < 0.001) and TLG (R = 0.800, R2 = 0.654, p < 0.001) were positively correlated with the maximum diameter of the tumor. Conclusion In our study, statistically significant positive correlations were found between SUVmax, SUVmean, SUVpeak, MTV, and TLG and the maximum diameter of PSP. We found that the maximum diameter of the tumor is associated with an increase in FDG uptake in PSP, reflecting a potential correlation between lesion diameter and PET metabolic parameters, indicating a link between structural features and metabolic activity.